Maternal mental health research in Malawi: Community and healthcare provider perspectives on acceptability and ethicality - Myness Kasanda Ndambo; Martyn Pickersgill; Christopher Bunn; Robert C. Stewart; Eric Umar; Maisha Nyasulu; Andrew M. McIntosh; Lucinda Manda-Taylor (Elsevier, 2023)
Maternal mental health (MMH) is recognised as globally significant. The prevalence of depression and factors associated with its onset among perinatal women in Malawi has been previously reported, and the need for further research in this domain is underscored. Yet, there is little published scholarship regarding the acceptability and ethicality of MMH research to women and community representatives. The study reported here sought to address this in Malawi by engaging with communities and healthcare providers in the districts where MMH research was being planned. Qualitative data was collected in Lilongwe and Karonga districts through 20 focus group discussions and 40 in-depth interviews with community representatives and healthcare providers from January through April 2021. All focus groups and interviews were audio recorded, transcribed verbatim (in local languages Chichewa and Tumbuka), translated into English, and examined through thematic content analysis. Participants' accounts suggest that biopsychosocial MMH research could be broadly acceptable within the communities sampled, with acceptability framed in part through prior encounters with biomedical and public health research and care in these regions, alongside broader understandings of the import of MMH. Willingness and consent to participate do not depend on specifically biomedical understandings of MMH, but rather on familiarity with individuals regarded as living with mental ill-health. However, the data further suggest some 'therapeutic misconceptions' about MMH research, with implications for how investigations in this area are presented by researchers when recruiting and working with participants. Further studies are needed to explore whether accounts of the acceptability and ethicality of MMH research shift and change during and following research encounters. Such studies will enhance the production of granular recommendations for further augmenting the ethicality of biomedical and public health research and researchers' responsibilities to participants and communities.